Performance of unit trust funds between conventional and Islamic funds in Malaysia using data envelopment analysis / Nahamizun Maamor ... [et al.] - Maamor, Nahamizun; Ariffin, Anas Fathul; Kin, Teoh Yeong; Abu Hasan, Suzanawati (UiTM Cawangan Perlis, 2021)
This study aims to analyse the current performance of unit trust funds between conventional and Islamic funds using data envelopment analysis because most Malaysians are incapable to distinguish between conventional and Islamic unit trust funds performances since they tend to assume both funds perform similarly. This paper uses 20 authorised funds by the Securities Commission Malaysia (SC) for three years by using trailing data that consists of volatility element as input and total return as output. Indeed, the funds selected do not mix asset classes of funds, instead relying solely on equity funds to create a fair and reasonable ranking. The study employs Data Envelopment Analysis by testing two different models, namely Charnes, Cooper, and Rhodes input oriented (CCR-I) model and Banker, Charnes, and Cooper input oriented (BCC-I) model. The use of two models in this study is to ensure that the results of the ranking analysis are more accurate and precise. Both models employ the input-oriented model function as a means of maximising efficiency in order to increase the number of fairies. The efficiency of Islamic funds is more consistent than that of conventional funds for both models, as several Islamic funds maintain their position at the top of the efficient rank. However, there is a significant increase in conventional funds because 80% of the selected conventional funds that are not efficient in the CCR-I model achieve the efficiency level in the BCC-I model. As a result, there are four unit trust funds that are consistent in occupying efficiency level when tested for both CCR-I model and BCC-I model whereby three out of four are Islamic funds while the other is conventional fund. The Islamic funds consist of Apex Dana Aslah, BIMB i Growth Fund, and Maybank Malaysia Growth-I Fund while KAF Tactical Fund is conventional fund. Ultimately, it is concluded that Islamic funds perform better than conventional funds in Malaysia for the 3 years period ending 31 March 2021.